Impelementasi dan Pengaruh Program Keluarga Harapan (PKH) Pada Tingkat Pendidikan dan Kesehatan Keluarga Sangat Miskin - Yusyifa Nurfaridah; Abdul Maqin (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2021)
Rapid population development can cause many complex problems that occur in society, including poverty. Various efforts have been made by the government to overcome the problem of poverty, one of the efforts made by the government is to issue a Family Hope Program (PKH) for very poor households (RTSM). This study aims to determine the implementation and influence of the family of hope program on the level of education and health in Mandalasari Village. The method used in this research is descriptive quantitative primary data and data collection techniques through interviews, observation and documentation. Results Based on the research, it shows that the influence of the Family Hope Program (PKH) in Mandalasari Village, Cipatat District, West Bandung has a greater influence on the level of education than the level of health. Among other things, the amount of PKH, consumption expenditure, and the number of school children have a partial effect on education. And, there is only one that has a partial effect, namely the number of sick days on health. The processed results show that the variables used have a simultaneous effect on education and health. It is hoped that through this research the government and the public can understand more about education and health for the poor which will ultimately break the chain of poverty in the long term.